Sill Propagation and Climbing in Layered Crystalline Host-Rocks: Examples from Saucer-Shaped Sills of The Faroe Islands - Hansen, Jogvan (European Journal of Applied Sciences, 2024)
Mafic sills, which commonly occur in layered sedimentary and crystalline settings worldwide, may occur as sub-lateral sheets or as saucer-shaped bodies. Values and distributions of Young’s Modulus within their ambient host-rocks determine their mode of emplacement. Current models on development of saucer-shaped sills depict either melt propagation from single sources along sub-lateral relatively weak layers, from which they abruptly climb/transgress through stronger layers at intervals, or they may evolve by radial melt propagation/intrusion from one or more sources, while gradually/continuously ascending/climbing through strong and weak layers alike. The first model invokes involvement of sill overburdens and overlying free surfaces, while the latter envisages closed igneous systems, where host-rocks both above and below the advancing magmas are affected without involvement of overlying free surfaces. Margins of saucer-shaped sills at various stages of developments, cropping out in the Faroe-Islands, offer some new insights into sill evolvement in layered crystalline host-rocks. This study suggests that the slightly upward-curving geometries of Faroese sills stem from initial radial propagations/intrusions of thin magma fronts, where systematic depth-dependent variations of Young’s Modulus in the Earth’s crust governed gradual and continuous climbing of these. Some of their melts likely propagated initially as lobes or thin magma-fingers in a mole-like fashion before coalescing, without noticeably affecting the overlying free surfaces prior to the main inflation phases.